(untitled) (International journal of artificial intelligence, 2026)
The theory of foreign language teaching plays a crucial role in shaping effective language learning and instructional practices. It provides a scientific and methodological foundation for understanding how languages are acquired, taught, and assessed in diverse educational contexts. This theory integrates insights from linguistics, psychology, pedagogy, and sociology to explain the cognitive, emotional, and social processes involved in foreign language learning. The practical significance of foreign language teaching theory lies in its application to real classroom situations. It guides teachers in selecting appropriate teaching methods, designing syllabi, choosing instructional materials, and assessing learners’ progress effectively. For example, communicative language teaching emphasizes interaction and real-life communication, while cognitive and constructivist approaches focus on learner autonomy and meaningful learning. Moreover, the theory helps educators address common challenges such as learner anxiety, motivation loss, and differences in learning styles. By applying theoretical principles in practice, teachers can create learner-centered, inclusive, and effective learning environments. Therefore, the theory of foreign language teaching not only explains how languages are learned but also significantly improves the quality and outcomes of language education.